pqsfinder: an exhaustive and imperfection-tolerant search tool for potential quadruplex-forming sequences in R - Hon, Jirí; Martínek, Tomáš; Zendulka, Jaroslav; Lexa, Matej (Bioinformatics (Oxford, England), 2017)
MOTIVATION: G-quadruplexes (G4s) are one of the non-B DNA structures easily observed in vitro and assumed to form in vivo. The latest experiments with G4-specific antibodies and G4-unwinding helicase mutants confirm this conjecture. These four-stranded structures have also been shown to influence a range of molecular processes in cells. As G4s are intensively studied, it is often desirable to screen DNA sequences and pinpoint the precise locations where they might form. RESULTS: We describe and have tested a newly developed Bioconductor package for identifying potential quadruplex-forming sequences (PQS). The package is easy-to-use, flexible and customizable. It allows for sequence searches that accommodate possible divergences from the optimal G4 base composition. A novel aspect of our research was the creation and training (parametrization) of an advanced scoring model which resulted in increased precision compared to similar tools. We demonstrate that the algorithm behind the searches has a 96% accuracy on 392 currently known and experimentally observed G4 structures. We also carried out searches against the recent G4-seq data to verify how well we can identify the structures detected by that technology. The correlation with pqsfinder predictions was 0.622, higher than the correlation 0.491 obtained with the second best G4Hunter. AVAILABILITY AND IMPLEMENTATION: http://bioconductor.org/packages/pqsfinder/ This paper is based on pqsfinder-1.4.1. CONTACT: lexa@fi.muni.cz. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.
Keywords: algoritmy; Software; software; G-kvadruplexy; sekvenční analýza DNA; genomika; Genomics; Algorithms; G-Quadruplexes; Sequence Analysis, DNA